Considerations in permanent implantation of peripheral nerve stimulation (PNS) for chronic neuropathic pain: An international cross‐sectional survey of implanters. Issue 5 (24th February 2022) - Li, Alice H.; Gulati, Amitabh; Leong, Michael S.; Aggarwal, Anuj K.; Salmasi, Vafi; Spinner, David; Ottestad, Einar
Abstract: Aim: Novel minimally invasive short‐term and long‐term peripheral nerve stimulation (PNS) systems have revolutionized targeted treatment of chronic neuropathic pain. We present an international survey of PNS‐implanting pain physicians to assess what factors they consider when offering permanent PNS. Methods: This cross‐sectional study consisted of a survey (Qualtrics) that was distributed to PNS‐implanting physicians in a device supplier's entire email database on November 13, 2020, with 3 weeks of response time. Physicians' contact information in the form of their email addresses had been previously collected by the supplier upon device distribution with permission to use survey responses for research. Results: Of 2032 database physicians, 40 physicians representing 37 institutions responded to the survey. The most common application of PNS was mononeuropathic pain (57%). The most frequently targeted nerve was the suprascapular nerve (29%). 14% of physicians reported 81–100% of their implants were dual‐lead. The representative physicians ranged broadly in their most frequently targeted nerves. Although mononeuropathic pain was the most common indication for PNS, there was still varied response regarding other indications such as CRPS and post‐surgical chronic pain. Conclusion: In context of a low response rate, identifying such factors can help update the prevailing treatment algorithm for interventional therapies, assist pain physicians in better identifying which patients are the best candidates for PNS, and inform future clinical trial design on PNS efficacy.